A reversible and highly selective phosphorescent sensor for Hg2+ based on iridium (III) complex. Issue 49 (9th December 2015) - Mei, Qunbo; Hua, Qingfang; Tong, Bihai; Shi, Yujie; Chen, Chen; Huang, Wei
Abstract: A novel reversible phosphorescent sensor for Hg 2+ based on a neutral iridium (III) complex Ir(TBT)2 (pic) (TBT=2-thiophen-2-yl-benzothiazole, pic=picolinate) has been synthesized and characterized. Ir(TBT)2 (pic) displayed relatively strong phosphorescent nearly centered at about 600 nm. Upon addition of acetonitrile (CH3 CN) solution of Hg 2+, the dichloromethane (DCM) solution of Ir(TBT)2 (pic) gave a visual color change from orange to yellow and significant phosphorescent quenching. It can serve as a highly selective sensor for Hg 2+ with naked-eye detection. The sensor allow determination of Hg 2+ in the working range of 4.0 μM–12.0 μM with a detection limit of 1.04 μM. When mixing with Hg 2+, Ir(TBT)2 (pic) interacted with Hg 2+ in a 1:2 stoichiometry via a coordination bond interaction between the sulfur atom and Hg 2+ . The phosphorescent chemosensor exhibited excellent selectivity and sensitivity for Hg 2+ detection. The spectral response of Ir(TBT)2 (pic) toward Hg 2+ was proved to be reversible. Graphical abstract: